2004
DOI: 10.1109/tcst.2004.825135
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Disturbance Observer for Multivariable Systems and Its Application to Magnetic Bearing Systems

Abstract: Abstract-This paper proposes a new nonlinear-disturbance observer for multivariable minimum-phase systems with arbitrary relative degrees. The model uncertainties and the system nonlinearities are treated as disturbances. The estimation of individual disturbances is independent of each other and the derivatives of the disturbances can be independently estimated. The proposed formulation is inspired by the variable structure-control method and adaptive algorithms where the a priori information concerning the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…The neural network disturbance observer is designed as (15), the nonlinear disturbance observer is designed as (24), and the parameter updated law of the RBFNN is chosen as (43). Then, the adaptive neural fault tolerant control law is proposed as (39).…”
Section: Substituting (39) Into (38) Yieldṡmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural network disturbance observer is designed as (15), the nonlinear disturbance observer is designed as (24), and the parameter updated law of the RBFNN is chosen as (43). Then, the adaptive neural fault tolerant control law is proposed as (39).…”
Section: Substituting (39) Into (38) Yieldṡmentioning
confidence: 99%
“…The general framework was studied for the DOBC of nonlinear systems with disturbances in [42]. In [43], a nonlinear disturbance observer was proposed for a multivariable minimum-phase system which has arbitrary relative degrees. The disturbance attenuation and rejection problem was studied for a class of MIMO nonlinear systems with unknown disturbance in [44].…”
Section: Introductionmentioning
confidence: 99%
“…In [28], nonlinear-disturbance observer was proposed for multivariable minimum-phase systems with arbitrary relative degrees. The nonlinear disturbance observer for robotic manipulators was developed in [29].…”
Section: Introductionmentioning
confidence: 99%
“…A new class of nonlinear PID predictive control scheme was proposed based on disturbance observers in [20]. In [21], a new nonlinear-disturbance observer (NDO) was proposed for multivariable minimum-phase systems with arbitrary relative degrees. Applications have shown that disturbance observers can enhance the disturbance attenuation and performance robustness.…”
Section: Introductionmentioning
confidence: 99%
“…A new NDO for robotic manipulators was also derived in [23]. However, the SMC strategy associated with disturbance observer has not been developed in [19,21,23].…”
Section: Introductionmentioning
confidence: 99%